Duodenal ulcer healing after presentation with haemorrhage. Issue 11 (November 1986) - Murray, W R; Laferla, G; Cooper, G; Archibald, M
Abstract : Forty patients who were managed conservatively after haemorrhage from an endoscopically verified duodenal ulcer were randomised at discharge from hospital to enter a blind study of ranitidine therapy (150 mg bd) versus a placebo tablet. The patients were re-endoscoped after four weeks, ulcer status defined and the trial code broken revealing that five of 20 placebo patients had healed their duodenal ulcer compared with 16 of 20 ranitidine patients (p = 0.001). Lifestyle parameters of both groups improved during the study period but no directly related benefit in duodenal ulcer healing could be shown. We conclude that effective anti-ulcer therapy, such as ranitidine, is required to heal a duodenal ulcer which presents with haemorrhage.